Evaluating the Influence of Barriers to Environmental Sustainability on Environmental Management Accounting in the Food and Beverage Manufacturing Firms in Durban, South Africa - Nzama, Smangele; Olarewaju, Odunayo Magret; Arise, Omolola A (The Journal of Accounting and Management, 2023)
The purpose of this study is to investigate how barriers to environmental sustainability influence the implementation of environmental management accounting in the food and beverage manufacturing firms in Durban, South Africa. Most professions make extensive use of environmental sustainability. However, research on environmental sustainability difficulties in the context of environmental management accounting in food and beverage manufacturing enterprises is limited. In this study, the quantitative research approach was applied, and convenience sampling was used to select study participants. The study obtained primary data from participants who work as finance managers, management accountants, factory accountants, and chief accountants in food and beverage manufacturing firms. The data was analyzed using SPSS. A total of 128 questionnaires were administered, with 124 filled correctly and evaluated. A Pearson's correlation research and regression analysis were performed. The Pearson's correlation coefficient findings show a statistically significant relationship between barriers to environmental sustainability and environmental management accounting in food and beverage manufacturing enterprises at (r = .250, p < 0.0005). According to the results of a regression study, the independent variable, barriers to sustainability, is a major predictor of environmental management accounting, B= 0.442, p< 0.05. The study suggests that firms within the food and beverage sector must resolve barriers to environmental sustainability in order to successfully implement environmental management accounting practices in their operations.